THE PROBLEM OF EVOLUTIONARY DEVELOPMENT OF IVAN FRANKO’S AESTHETIC CONSCIOUSNESS THROUGH THE PRISM OF HIS STORY "BOA CONSTRICTOR" TEXTUAL ANALYSIS - HOLOD, R. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The attempts to identify the main vectors of the evolution of I. Franko’s individual creative methods on the basis of the textological analysis of three versions of his story "Boa Constrictor", and the similarly-named work of the German writer K. Shpindler were made in the article. The author notices interconnection between the development of I. Franko’s creative methods and the establishment of the realistic creation type in the Ukrainian and world literature.